Occupational injuries reported in a Canadian university setting: a five year retrospective study. - Jaskolka JV; Andrews DM; Harold L (Work, 2009)
Research examining occupational injuries of university employees is limited, with previous work in the education sector focusing primarily on students and athletic teams. The current study examined occupational injuries over a five year period to determine the magnitude and nature of occupational injuries in a Canadian university with a view to developing prevention and intervention strategies. Findings suggested that women in full-time positions reported more injuries than men, and that as employees' level of experience increased the incidence of injury decreased. Analysis of injury characteristics revealed that the fingers, back and hand were the most frequently injured sites typically as a result of being struck or caught by an object, a slip/trip, or overexertion. These injuries resulted predominantly in an acute soft tissue injury requiring medical attention. Over the five year study period, food services, housekeeping and clerical staff filed the greatest number of accident/incident reports. Future investigations should employ a prospective approach which would allow researchers to determine variables of interest, ensure adequate data collection, and aim to improve the generalizability of research findings in this area.